2015
DOI: 10.1002/we.1830
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic load control in horizontal axis wind turbines with combined aeroelastic tailoring and trailing‐edge flaps

Abstract: This paper presents an aeroservoelastic modeling approach to investigate dynamic load alleviation in large wind turbines with composite blades and trailingedge aerodynamic surfaces. The tower and rotating blades are modeled using geometrically-nonlinear composite beams, and linearized about reference rotating conditions with potentially arbitrarily-large structural displacements. The aerodynamics of the rotor are represented using a linearized unsteady vortexlattice method and the resulting aeroelastic system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…In this study, a planar wake is sought and it has been shown that the computation of aerodynamic loads (used here for the fluid-structure coupling) displayed little differences with free-wake models [32]. Figure 3 and further details can be found in [36]. The resulting coupled LTI EoM characterizing the full aeroelastic system is…”
Section: Aeroelastic Formulationmentioning
confidence: 97%
“…In this study, a planar wake is sought and it has been shown that the computation of aerodynamic loads (used here for the fluid-structure coupling) displayed little differences with free-wake models [32]. Figure 3 and further details can be found in [36]. The resulting coupled LTI EoM characterizing the full aeroelastic system is…”
Section: Aeroelastic Formulationmentioning
confidence: 97%
“…The external forces and moments are represented by Q ext and are used in the coupling with aerodynamics. The primary variable η contains all the nodal displacements and rotations, ν contains the rigid-body motions and λ are the Lagrange multipliers (Ng et al, 2015). The transformation T tr (t) map base motions and the additional kinematics due to rotation of tower moment arm onto the rotor hub.…”
Section: Three-dimensional Multi-body Structural Dynamicsmentioning
confidence: 99%
“…After a convergence and numerical verification study in Ng et al (2015), the finite element discretisation of the structural model contains a total of 11 tower elements including platform and 12 elements per blade, as illustrated in Figure 2. The characteristics of the turbine blade are defined using a linear interpolation of the documented properties in J. M. Jonkman et al (2009).…”
Section: Numerical Verification and Implementationmentioning
confidence: 99%
See 2 more Smart Citations